Slavophile empire : Imperial Russia's illiberal path - Engelstein, Laura (Ithaca : Cornell University Press, 2009)
Annotation Twentieth-century Russia, in all its political incarnations, lacked the basic features of the Western liberal model: the rule of law, civil society, and an uncensored public sphere. In Slavophile Empire, the leading historian Laura Engelstein pays particular attention to the Slavophiles and their heirs, whose aversion to the secular individualism of the West and embrace of an idealized version of the native past established a pattern of thinking that had an enduring impact on Russian political life. Imperial Russia did not lack for partisans of Western-style liberalism, but they were outnumbered, to the right and to the left, by those who favored illiberal options. In the book's rigorously argued chapters, Engelstein asks how Russia's identity as a cultural nation at the core of an imperial state came to be defined in terms of this antiliberal consensus. She examines debates on religion and secularism, on the role of culture and the law under a traditional regime presiding over a modernizing society, on the status of the empire's ethnic peripheries, and on the spirit needed to mobilize a multinational empire in times of war. These debates, she argues, did not predetermine the kind of system that emerged after 1917, but they foreshadowed elements of a political culture that are still in evidence today.
Combined underdevelopment : discipline and the law in Imperial and Soviet Russia -- Revolution and the theater of public life : the triumph of extremes -- The dream of civil society : the law, the state, and religious toleration -- Holy Russia in modern times : the Slavophile quest for the lost faith -- Orthodox self-reflection in a modernizing age : the case of Ivan and Natal'ia Kireevskii -- Between art and icon : Aleksandr Ivanov's Russian Christ -- The old Slavophile steed : failed nationalism and the philosophers' Jewish problem.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Political culture -- Russia -- History -- 19th century; Slavophilism -- Russia -- History -- 19th century; Liberalism -- Russia -- History -- 19th century; Russians -- Ethnic identity -- History -- 19th century; Nationalism -- Russia -- History -- 19th century; Religion and state -- Russia -- History -- 19th century; Russia -- Politics and government -- 1801-1917.; Russia -- Intellectual life -- 1801-1917.; Slavophilisme -- Russie -- Histoire -- 19e siècle.; Libéralisme -- Russie -- Histoire -- 19e siècle.; Russes -- Identité ethnique -- Histoire -- 19e siècle.; Nationalisme -- Russie -- Histoire -- 19e siècle.; Religion et État -- Russie -- Histoire -- 19e siècle.; Russie -- Politique et gouvernement -- 1801-1917.; Russie -- Vie intellectuelle -- 1801-1917.; HISTORY -- Europe -- Russia & the Former Soviet Union; Intellectual life; Liberalism; Nationalism; Political culture; Politics and government; Religion and state; Russians -- Ethnic identity; Slavophilism; Russia; 1800-1917; History